The Story of Sese nTaola: Introduction and translation - Coté, Joost; Adriani, Nicolaus (LOBO: Annals of Sulawesi Research, 2022)
The Story of Sese nTaola belongs to the literature of the Bare'e- speaking people of the state of Tojo, the coastal region bounded in the east by Cape Api, and in the west by the Malei River (about 120.52 deg east of Gorontalo). The story was written up in August 1898 as told by i Parala, usually known by his technical name of Ta Aji (uncle of A), a Sausu man by birth, married into the To Lage living around the mouth of the Poso River, where he has been resident for many years.